2020
DOI: 10.1590/s1519-99402121062020
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stress alters the basal value of serum proteins in laying hens

Abstract: This study aimed to evaluate the effect of thermal stress on the physiological and metabolic parameters in laying hens and the microbiological quality of eggs. The experiment was performed with 50 Rhode Island Red hens in the initial laying phase, under standard diet, lodged in 20 m² stalls under controlled temperature, for 30 days. The laying hens were randomly divided into two groups: G1 - the control group, which contained 10 hens exposed to the temperature of 17 ºC; G2 - the treatment group, which containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Due to the absence of sweat glands, chickens rely on respiration rates to maintain their body temperature 20 . Furthermore, dehydration is a common cause of high ambient temperature that results in increasing serum protein in chickens 21 . In the present study, CHS birds showed higher RT and plasma total protein in comparison to the NT.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the absence of sweat glands, chickens rely on respiration rates to maintain their body temperature 20 . Furthermore, dehydration is a common cause of high ambient temperature that results in increasing serum protein in chickens 21 . In the present study, CHS birds showed higher RT and plasma total protein in comparison to the NT.…”
Section: Discussionmentioning
confidence: 99%